Implementasi Gerakan Literasi Sekolah Tahap Pembelajaran dalam Pengembangan Berpikir Historis Siswa dari Perspektif Literasi Kritis di SMA Negeri 2 Kota Mojokerto - Achmad Dicky Setyawan; Moch. Nurfahrul Lukmanul Khakim (Jurnal Artefak, 2026)
This research is motivated by the demands of the school literacy movement (SLM) to integrate critical literacy in history learning and the low historical thinking skills of students. The main objective of this research is to analyze the implementation of the literacy school movement in the learning stage developing the historical thinking skills of students in grades X IIS (Social Sciences) and XI IIS at State Senior High School 2 Mojokerto City. The method used in compiling this research is a qualitative research method. The results of this study empirically prove that, in the context of SLM, critical literacy is not only a supplement, but also makes teachers no longer the sole source of truth, rather becoming facilitators who shape and develop students' historical thinking through critical questions and answers. The conclusion of this study is that the SLM learning stage in developing historical thinking, the indicators of findings based on Stéphane Lévesque's concept of historical thinking, history teachers in this school are transformed into critical discussion facilitators and learning resources and students are able to construct their own narratives and analyze historical events based on evidence they find outside of textbooks.